Baduanjin exercise: A potential promising therapy toward osteoporosis - Sun, Chuanrui; Qi, Baoyu; Huang, Xinyi; Chen, Ming; Jin, Zikai; Zhang, Yili; Zhu, Liguo; Wei, Xu (Frontiers in Medicine, 2022)
Purpose: Baduanjin (BDJ) exercise is a traditional exercise that combines breathing, body movement, meditation and awareness to help delay the onset and progression of senile degenerative musculoskeletal diseases, such as osteoporosis (OP). The aim of this meta-analysis is to evaluate the efficacy, and preliminarily infer the effective mechanism of BDJ exercise in the treatment of osteoporosis. Methods: We identified relevant randomized controlled trials (RCTs) through 8 databases, and compared BDJ exercise with the control groups (including blank control and conventional treatment intervention). The main outcome measure was bone mineral density (BMD), the additional outcome measures were visual analogue scale (VAS), Berg balance scale (BBS), serum Calcium (Ca), serum Phosphorus (P), serum Alkaline phosphatase (ALP), and serum bone gla protein (BGP). Meta-analysis and trial sequence analysis (TSA) were performed using RevMan 5.4, Stata 16.0, and TSA 0.9. In addition, we also initially summarized the possible mechanism of BDJ exercise in the treatment of OP. Results: 13 RCTs involving 919 patients were included in the analysis. For postmenopausal osteoporosis, BDJ exercise alone and BDJ exercise combined with conventional treatment can improve the BMD of lumbar spine. BDJ exercise alone can improve Ca and ALP. BDJ exercise combined with conventional treatment can improve balance (BBS) and BGP. For senile osteoporosis, BDJ exercise alone and BDJ exercise combined with conventional treatment can improve balance (BBS). BDJ exercise combined with conventional treatment can improve the BMD of hip and pain (VAS). For primary osteoporosis, BDJ exercise combined with conventional treatment can improve the BMD of lumbar spine and femoral neck. Conclusion: BDJ exercise may be beneficial to improve BMD, relieve pain, and improve balance ability, serum BGP, as well as serum ALP in patients with OP, but differences occur due to various types of OP. Due to the low quality of research on the effect and mechanism of BDJ exercise in the treatment of OP, high-quality evidence-based research is still needed to provide reliable supporting evidence.